Validity and reliability of the session-RPE method for quantifying training load in karate athletes - Tabben, M.; Tourny, C.; Haddad, M.; Chaabane, H.; Chamari, K.; Coquart, J. B. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: To test the construct validity and reliability of the session rating of perceived exertion (sRPE) method by examining the relationship between RPE and physiological parameters (heart rate: HR and blood lactate concentration: [La --] ) and the correlations between sRPE and two HR--based methods for quantifying internal training load (Banister's method and Edwards's method) during karate training camp.